Control of Essential Facilities by State-Owned Enterprises as an Abuse of Dominant Position: An Indonesian Competition Law Perspective - David Al Fath Yustino; Hanif Nur Widhiyanti; Amelia Sri Kusuma Dewi (International Journal of Business, Law, and Education, 2026)
State-owned enterprises (SOEs) occupy a constitutionally significant position in Indonesia because they are entrusted with managing sectors of production that are important to the state and affect the livelihood of the public. In many network industries, however, SOEs also control facilities that are technically, economically, or legally indispensable for competitors to enter and operate in adjacent or downstream markets. This article examines whether and under what conditions the control of essential facilities by SOEs may constitute an abuse of dominant position under Indonesian competition law. Using normative legal research, this study combines statutory, conceptual, comparative, and case approaches. It analyses Article 33 of the 1945 Constitution, Law No. 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition, the SOE legal framework, the Essential Facilities Doctrine, and the Indonesian Competition Commission Decision No. 02/KPPU-I/2013 concerning PT Pelabuhan Indonesia II (Persero). The article argues that SOE control over strategic infrastructure is not unlawful per se where it is grounded in a public mandate and implemented for public-interest objectives. Nevertheless, refusal of access, discriminatory access conditions, tying access to the use of affiliated services, disproportionate access fees, and self-preferencing may transform lawful control into an exclusionary abuse where such conduct forecloses competitors or raises their operating costs without objective justification. The article proposes a five-factor analytical test: essentiality of the facility, dominance of the facility controller, exclusionary or discriminatory conduct, demonstrable anticompetitive effect, and absence of objective justification. It concludes that Indonesian law should explicitly incorporate clearer essential-facility standards and that KPPU should issue specific guidelines to reconcile SOE public mandates with competition neutrality.